COG Complex Complexities: Detailed Characterization of a Complete Set of HEK293T Cells Lacking Individual COG Subunits - Bailey Blackburn, Jessica; Pokrovskaya, Irina; Fisher, Peter; Ungar, Daniel; Lupashin, Vladimir V. (Frontiers in Cell and Developmental Biology, 2016)
The Conserved Oligomeric Golgi complex is an evolutionarily conserved multisubunit tethering complex (MTC) that is crucial for intracellular membrane trafficking and Golgi homeostasis. The COG complex interacts with core vesicle docking and fusion machinery at the Golgi; however, its exact mechanism of action is still an enigma. Previous studies of COG complex were limited to the use of CDGII (Congenital disorders of glycosylation type II)-COG patient fibroblasts, siRNA mediated knockdowns, or protein relocalization approaches. In this study we have used the CRISPR approach to generate HEK293T knock-out (KO) cell lines missing individual COG subunits. These cell lines were characterized for glycosylation and trafficking defects, cell proliferation rates, stability of COG subunits, localization of Golgi markers, changes in Golgi structure, and N-glycan profiling. We found that all KO cell lines were uniformly deficient in cis/medial-Golgi glycosylation and each had nearly abolished binding of Cholera toxin. In addition, all cell lines showed defects in Golgi morphology, retrograde trafficking and sorting, sialylation and fucosylation, but severities varied according to the affected subunit. Lobe A and Cog6 subunit KOs displayed a more severely distorted Golgi structure, while Cog2, 3, 4, 5 and 7 knock outs had the most hypoglycosylated form of Lamp2. These results led us to conclude that every subunit is essential for COG complex function in Golgi trafficking, though to varying extents. We believe that this study and further analyses of these cells will help further elucidate the roles of individual COG subunits and bring a greater understanding to the class of MTCs as a whole.